EKSPLORASI ETNOMATEMATIKA PADA TRADISI MENGONJI BERAYAK DI DESA PULAU KOMANG, SENTAJO RAYA, KABUPATEN KUANTAN SINGINGI - Silvia, Vioni; Fendrik, Muhammad; Adi Putra, M. Jaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Culture and education are closely interconnected in shaping students' character and thinking abilities. Culturally-based learning helps link lesson content with the values, habits, and practices embedded in society, making the learning process more contextual, meaningful, relevant, and easier to understand. Mathematics, as an essential subject for developing logical thinking skills, is often considered difficult due to its abstract nature. Therefore, the ethnomathematics approach serves as an alternative solution by integrating cultural elements into mathematics learning, making it more accessible while also preserving local cultural values. This study aims to explore the application of ethnomathematics in the Mengonji Berayak tradition in Pulau Komang Village, Sentajo Raya District, Kuantan Singingi Regency. The method used is a qualitative-exploratory approach with an ethnographic design. Data collection was conducted through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results show that the Mengonji Berayak tradition contains six ethnomathematical activities: counting, locating, measuring, designing, playing, and explaining. Mathematical concepts such as measurement, arithmetic operations, and geometry were also identified, which can be utilized as contextual and culturally-based learning resources. These findings indicate that ethnomathematical concepts are present in the Mengonji Berayak tradition and can be integrated into mathematics learning, particularly at the elementary school level in Phase B.